2017
DOI: 10.18632/oncotarget.19644
|View full text |Cite
|
Sign up to set email alerts
|

SNX10 promotes phagosome maturation in macrophages and protects mice againstListeria monocytogenesinfection

Abstract: Listeria monocytogenes (L. monocytogenes), which is a facultative intracellular bacterial pathogen that causes listeriosis, is widely used to study the mammalian immune response to infection. After phagocytosis by professional phagocytes, L. monocytogenes is initially contained within phagosomes, which mature into phagolysosomes, where the bacteria are degraded. Although phagocytosis and subsequent phagosome maturation is essential for the clearance of infectious microbial pathogens, the underlying regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Accordingly, SNX1 organizes a tubular network during establishment of the Salmonella -containing vacuole (SCV; Bujny et al, 2008 ), while depletion of SNX3 leads to reduced formation of Salmonella -induced filaments ( Braun et al, 2010 ). Recently, Chlamydia trachomatis was shown to hijack SNX5, resulting in disrupted retromer trafficking ( Elwell et al, 2017 ; Paul et al, 2017 ), whereas SNX10 was found to promote phagosome maturation and protect against infection with Listeria monocytogenes ( Lou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SNX1 organizes a tubular network during establishment of the Salmonella -containing vacuole (SCV; Bujny et al, 2008 ), while depletion of SNX3 leads to reduced formation of Salmonella -induced filaments ( Braun et al, 2010 ). Recently, Chlamydia trachomatis was shown to hijack SNX5, resulting in disrupted retromer trafficking ( Elwell et al, 2017 ; Paul et al, 2017 ), whereas SNX10 was found to promote phagosome maturation and protect against infection with Listeria monocytogenes ( Lou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…SNX10 has been found to play an important role in embryonic development [ 11 ] , alcohol-induced liver injury and steatosis [ 13 ] , osteoclast formation and resorption activity [ 14 , 15 ] , colorectal cancer [ 16 ] , and phagosome maturation in macrophages [ 17 ] . However, little is known about its role in cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…SNX10 , a member of the family of sorting nexins, is a protein involved in intracellular protein sorting, trafficking, and signal transduction (36). Moreover, SNX10 has been reported to regulate endosomal morphology, which might be crucial for macrophage function, including phagocytosis and digestion of pathogens, inflammatory response, and Ag presentation (37). The SCNN1A gene encodes for the α subunit of the epithelial sodium channel (ENaC), which plays a critical role in the ion and fluid regulation of the lung.…”
Section: Discussionmentioning
confidence: 99%